MyQiraat: An interactive Qiraat mobile application - Ishak S.F.; Zaki Z.M.; Mohamad K.A.; Bahrin M.A.M.; Roni N.H.A.; Musa M.A. (Institute of Electrical and Electronics Engineers Inc., 2024)
Indexed by WOS/ Scopus